Neutralizing Antibody Response to BBIBP-CorV in Comparison with COVID-19 Recovered, Unvaccinated Individuals in a Sample of the Pakistani Population - Javeria Aijaz; Shakir Hussain; Fouzia Naseer; Fatima Kanani; Sabiha Anis; Samreen Sarfaraz; Saima Saeed; Hina Farooq; Saba Jamal (Vaccines, 2022)
Fifty five percent of the Pakistani population is still unvaccinated with the two-dose protocol of COVID-19 vaccines. This study was undertaken to determine the seroconversion rate and antibody titers following the two-dose BBIBP-CorV protocol, and to compare these variables in unvaccinated, COVID-19 recovered individuals (total n = 180) at Indus Hospital and Health Network, Karachi. Pseudotyped lentivirus antibody neutralization assays and SARS-CoV-2 IgG Quant II (Abbott) immunoassays were performed 4-8 weeks following the second dose of the BBIBP-CorV or PCR positivity/onset of symptoms of COVID-19. Seroconversion rate, using neutralization assays, in vaccinated individuals was lower (78%) than that in unvaccinated, COVID-19-recovered individuals with moderate to severe infection (97%). Prior PCR positivity increased serocoversion rate to 98% in vaccinated individuals. Immunoassays did not, however, reveal significant inter-group differences in seroconversion rates (≥95% in all groups). Log10 mean antibody neutralizing titers following the two-dose BBIBP-CorV protocol (IC50 = 2.21) were found to be significantly less than those succeeding moderate to severe COVID-19 (IC50 = 2.94). Prior SARS-CoV-2 positivity significantly increased post-vaccination antibody titers (IC50 = 2.82). Similar inter-group titer differences were obtained using the immunoassay. BBIBP-CorV post-vaccination titers may, thus, be lower than those following natural, moderate to severe infection, while prior SARS-CoV-2 exposure increases these titers to more closely approximate the latter.